Sand mold material for casting chrome corundum as well as preparation method and application of sand mold material
By adopting sand-shaped materials with a double-layer structure of flexible layer and contact layer, the problems of strength reduction and corrosion in the existing technology of sand-shaped materials at high temperatures have been solved, and the high-temperature mechanical strength and corrosion resistance of zirconium chromium corundum products have been significantly improved, meeting the production needs of zirconium chromium corundum products.
Patent Information
- Application Number
- CN202411797736.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-21
AI Technical Summary
The existing sand-shaped materials are difficult to resist the erosion of zirconium chromium corundum melt at high temperatures above 2000℃, resulting in casting failure and the strength drops sharply at high temperatures, making it difficult to meet the production needs of zirconium chromium corundum products.
A sand-shaped material with a double-layer structure of flexible layer and contact layer is used. The flexible layer is composed of molten cast chromium oxide aggregate, α-alumina powder, zircon sand, mullite fiber, etc. The contact layer is composed of ρ-alumina powder, α-alumina powder, chromium powder, etc. Through reasonable proportioning and process processing, the high-temperature mechanical strength and corrosion resistance of the sand-shaped material are improved.
It significantly improves the mechanical strength and corrosion resistance of sand-shaped materials at high temperatures above 2000℃, extends the high-temperature stability during casting, reduces the risk of mold cracking, and improves the production success rate of zirconium chromium corundum products.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sand mold materials for refractory materials, and specifically relates to a sand mold material for molten-cast chrome corundum and a preparation method and application thereof. Background Art
[0002] Casting refractory materials, especially zirconium-chromium-corundum products, have key applications in the fields of steel, non-ferrous metals, glass, cement, and nuclear waste glass solidification Joule furnaces due to their excellent high temperature resistance, thermal shock resistance, and corrosion resistance. However, the production process of zirconium-chromium-corundum products is difficult, especially in the high-temperature casting process of 2000℃-2180℃. At present, China still relies on imports, which has become an important bottleneck restricting the development of related industries in my country, especially the nuclear industry.
[0003] The core challenge in the casting process is that the sand mold material cannot withstand the severe thermal shock and erosion of the high-temperature melt. Especially for large-sized castings, the sand mold is prone to breakage, resulting in casting failure. Existing sand mold technology is mainly based on silica sand (for example, CN112338818A discloses a silica sand mold using composite binders such as phosphate and water glass). Although its hardening speed and environmental adaptability have been improved, it is still difficult to resist the erosion of the melt at high temperatures above 2000°C.
[0004] In order to improve the high temperature resistance of sand molds, some studies have tried to use white corundum instead of silica sand (for example, CN115321940B discloses a sand mold with white corundum as aggregate and modified water glass as binder). Although the strength at room temperature has been improved, the water glass binder will produce a large amount of liquid phase at high temperature, resulting in a sharp drop in the high temperature strength of the sand mold.
[0005] In summary, there is still a gap in the special sand mold technology for ultra-high temperature fused-cast refractory materials such as zirconium-chromium-corundum. It is urgent to develop sand mold materials that can withstand the erosion of high-temperature melts above 2000°C and maintain sufficient high-temperature strength to break through the production bottleneck of fused-cast zirconium-chromium-corundum products. Summary of the invention
[0006] The invention provides a sand mold material for molten chrome corundum and a preparation method and application thereof, aiming to provide a sand mold material which has excellent high-temperature mechanical strength, can withstand high temperatures and resist high-speed impacts during casting.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is to provide a sand mold material, including a flexible layer and a contact layer, wherein the contact layer is coated on the surface of the flexible layer; in parts by weight,
[0008] The flexible layer comprises:
[0009] 20 to 50 parts of fused-cast chromium oxide aggregate of the first particle size, 10 to 30 parts of fused-cast chromium oxide aggregate of the second particle size, wherein the second particle size is smaller than the first particle size, 20 to 60 parts of α-alumina powder, 0 to 10 parts of zircon sand, 0 to 15 parts of mullite fiber, 0 to 15 parts of PVC pipe, 0.18 to 0.51 parts of bonding promoter, 5 to 25 parts of bonding agent, and 0 to 2.5 parts of polyoxyethylene alkylphenol ether;
[0010] The contact layer comprises:
[0011] 1 to 10 parts of ρ-alumina powder, 30 to 75 parts of α-alumina powder, 20 to 50 parts of chromium micropowder, 5 to 15 parts of zirconium oxide micropowder, 10 to 15 parts of aluminum sol, and 0.5 to 1 part of magnesium oxide micropowder.
[0012] In a possible embodiment, the first particle size ranges from 2.0 mm to 3.0 mm, and the second particle size ranges from 0.5 mm to 1 mm.
[0013] In a possible embodiment, the bonding promoter is composed of yttrium oxide and lanthanum oxide, wherein the mass ratio of yttrium oxide to lanthanum oxide is (0.5~1):1.
[0014] In a possible embodiment, the binder is composed of aluminum sol and zirconium sol, wherein the mass ratio of aluminum sol to zirconium sol is (1-3):(1-5).
[0015] In a possible embodiment, the particle sizes of the α-alumina powder, the chromium powder and the zirconium oxide powder are all ≤0.05 mm, and the particle size of the zircon sand is 45 μm to 100 μm.
[0016] In a possible embodiment, the fiber diameter of the mullite fiber is 0.5 mm to 0.1 mm, and the fiber length is 5 mm to 10 mm.
[0017] In a possible embodiment, the diameter of the PVC tube is 2.5 mm to 5.5 mm, and the length of the tube is 10 mm to 50 mm.
[0018] The present invention also provides a method for preparing a sand material, comprising the following steps:
[0019] Step 1: preparing a flexible layer, which comprises the following steps, in parts by weight: a) fully mixing 20 to 50 parts of a first-size fused-cast chromium oxide aggregate, 10 to 30 parts of a second-size fused-cast chromium oxide aggregate (the second size is smaller than the first size), 20 to 60 parts of α-alumina powder, 0 to 10 parts of zircon sand, 0 to 15 parts of PVC pipe, 0.18 to 0.51 parts of a bonding promoter, and 5 to 25 parts of a bonding agent to prepare an initial mixture; b) adding 0 to 15 parts of mullite fiber to the initial mixture of step a), and then adding 0 to 2.5 parts of polyoxyethylene alkylphenol ether, and rapidly stirring to prepare a flexible layer mixture; c) pressing the flexible layer mixture into a shape by a pressing device; d) placing the pressed flexible layer mixture in a drying kiln for drying to obtain a flexible layer;
[0020] Step 2: preparing a contact layer, by weight, comprising: uniformly mixing 1 to 10 parts of ρ-alumina powder, 30 to 75 parts of α-alumina powder, 20 to 50 parts of chromium powder, 5 to 15 parts of zirconium oxide powder, 10 to 15 parts of aluminum sol, and 0.5 to 1 part of magnesium oxide powder to prepare a contact layer mixture;
[0021] Step 3: composite molding, including the following steps: 1) applying the contact layer mixture in step 2 to the surface of the flexible layer in step 1; 2) placing the coated composite layer in a drying kiln to dry to obtain a sand mold material.
[0022] In a possible embodiment, the contact layer mixture in step 2 is applied to the surface of the flexible layer in step 1 to a height of 1 mm to 6 mm.
[0023] The invention also provides a mold, which adopts the above-mentioned sand mold material.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention adopts a sand mold material formed by a double-layer structure of a flexible layer and a contact layer, wherein the flexible layer is responsible for withstanding the high temperature environment and mechanical deformation during casting and heat preservation annealing. If the flexible layer is used alone, large particles on the surface are easily eroded by the high-temperature steel flow and rolled into the casting, causing inclusions. At the same time, the erosion of the steel flow will seriously reduce its mechanical strength. By adding a contact layer on the surface of the flexible layer, its mechanical structure can be well protected.
[0026] (2) The high-temperature sand mold template prepared with chromium oxide as the main raw material and reasonable grading not only has high high-temperature refractoriness, but also has good air permeability. The PVC pipe installed inside forms a microporous exhaust channel, which accelerates the exhaust of gas inside the casting and effectively prevents the template from cracking due to internal high-temperature air pressure.
[0027] (3) Using molten chromium oxide as the main raw material for sand molds and sol as a binder, the addition of low-melting-point raw materials is strictly controlled to reduce the amount of internal liquid phase. By adjusting the proportion of high-temperature bonding agents, the solid-phase sintering reaction between sand mold powders is promoted, thereby ensuring that the sand mold has excellent high-temperature stability.
[0028] (4) The present invention adds mullite fiber as a reinforcing phase to the sand mold material. Mullite fiber can effectively limit deformation caused by thermal expansion and contraction, improve stress conduction and dispersion, and enhance the material's ability to resist high-temperature erosion, thereby significantly improving the strength, thermal deformation resistance and service life of the sand mold plate. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0030] Example 1
[0031] A sand mold material for fused chrome corundum includes a flexible layer, wherein the flexible layer is composed of the following raw materials, measured in parts by weight:
[0032] Casting chromium oxide aggregate with a particle size of 2.0mm~3.0mm, of which the Cr2O3 content is greater than 80%, and the addition amount is 30 parts;
[0033] Cast chromium oxide aggregate with a particle size of 0.5mm~1mm, of which the Cr2O3 content is greater than 80%, and the addition amount is 15 parts;
[0034] α-alumina powder, particle size requirement ≤ 0.05mm, added amount 45 parts;
[0035] Zircon sand, particle size required is 45μm~100μm, added in 5 parts;
[0036] 0.31 parts of a bonding promoter, which is mainly composed of yttrium oxide and lanthanum oxide, and the mass ratio of yttrium oxide to lanthanum oxide is 1:2;
[0037] The amount of binder added is 18 parts, and the binder is mainly composed of aluminum sol and zirconium sol, and the mass ratio of aluminum sol to zirconium sol is 2:1.
[0038] The various components of the flexible layer are fully mixed according to the ratio of this embodiment to form a flexible layer mixture, and the uniformly stirred flexible layer mixture is pressurized by a 1000T friction press to form a flexible layer at a molding pressure of 220MPa. The pressed flexible layer is placed in a drying kiln for drying at 300°C for 18h and then used for later use.
[0039] Example 2
[0040] A sand mold material for molten chrome corundum comprises a flexible layer and a contact layer, wherein the raw material composition and the proportion of each component of the flexible layer are the same as those in Example 1.
[0041] The contact layer is composed of the following raw materials, in parts by weight:
[0042] ρ-alumina powder, added in an amount of 8 parts;
[0043] α-alumina powder, added in an amount of 50 parts;
[0044] Chromium powder, particle size requirement ≤ 0.05mm, added amount 25 parts;
[0045] Zirconia powder, particle size requirement ≤ 0.05mm, added amount 12 parts;
[0046] Aluminum sol, added in an amount of 5 parts;
[0047] Magnesium oxide powder, added in an amount of 0.8 parts;
[0048] The various components of the flexible layer are fully mixed according to the ratio of this embodiment to form a flexible layer mixture, and the uniformly stirred flexible layer mixture is pressurized by a 1000T friction press to form a flexible layer at a molding pressure of 220MPa. The pressed flexible layer is placed in a drying kiln for drying at 300°C for 18h and then used for later use.
[0049] The various component raw materials of the contact layer are fully mixed according to the ratio of this embodiment to form a contact layer mixture, and the contact layer mixture is applied to the working hot surface of the flexible layer, and the thickness of the applied contact layer is 2mm. The applied sand mold plate is placed in a drying kiln for drying at 230°C for 3h, and assembled into a sand mold after drying.
[0050] Example 3
[0051] A sand mold material for fused chrome corundum includes a flexible layer, which is composed of the following raw materials, measured in parts by weight:
[0052] Cast chromium oxide aggregate with a particle size of 2.0mm~3.0mm, Cr2O3 content>80%, added in an amount of 30 parts,
[0053] The particle size is 0.5mm~1mm fused-cast chromium oxide aggregate, the Cr2O3 content is greater than 80%, and the addition amount is 15 parts;
[0054] α-alumina powder, particle size requirement: ≤ 0.05mm, addition amount: 45 parts;
[0055] Zircon sand, particle size requirement: 45μm-100μm, added amount 5 parts;
[0056] Mullite fiber, fiber diameter: 0.5mm-0.1mm fiber length: 5mm-10mm, added amount 3 parts;
[0057] PVC tube, tube diameter: 1.5mm, tube length: 20mm, add 3 parts;
[0058] 0.31 parts of a bonding promoter, which is composed of yttrium oxide and lanthanum oxide, and the mass ratio of yttrium oxide to lanthanum oxide is 1:2;
[0059] The amount of the binder added is 18 parts, and the binder is mainly composed of aluminum sol and zirconium sol, and the mass ratio of aluminum sol to zirconium sol is 2:1;
[0060] Polyoxyethylene alkylphenol ether, 0.8 parts.
[0061] Chromium oxide aggregates with particle sizes of 2.0mm~3.0mm and 0.5mm~1mm, α-alumina powder, zircon sand, PVC pipe, binder, and bonding promoter are mixed according to the proportions in this embodiment, and a mixture is prepared after sufficient mixing. Mullite fiber according to the proportions in this embodiment is added to the stirred mixture, and then polyoxyethylene alkylphenol ether according to the proportions in this embodiment is added, and the flexible layer mixture is quickly stirred to prepare the flexible layer mixture, and the stirred flexible layer mixture is pressurized and molded by a 1000T friction press, and the molding pressure is 220MPa. The pressed flexible layer is placed in a drying kiln for drying at 300℃×18h, and is used for standby after drying.
[0062] Example 4
[0063] A sand mold material for molten chrome corundum includes a flexible layer and a contact layer. The raw material composition and the proportion of each component of the flexible layer are different from those of Example 3 in that the amount of PVC pipe added is 8 parts, and the remaining raw materials and proportions of the flexible layer are the same as those of Example 3.
[0064] The raw materials and proportions of the components of the contact layer are the same as those in Example 2.
[0065] According to the proportions in this embodiment, chromium oxide aggregates with particle sizes of 2.0mm~3.0mm and 0.5mm~1mm, α-alumina powder, zircon sand, PVC pipe, bonding promoter, and bonding agent are mixed, and a mixture is prepared after sufficient mixing. Then, mullite fiber according to the proportions in this embodiment is added to the stirred mixture, and polyoxyethylene alkylphenol ether according to the proportions in this embodiment is added, and the flexible layer mixture is quickly stirred to prepare the flexible layer mixture, and the stirred flexible layer mixture is pressurized and molded by a 1000T friction press, and the molding pressure is 220MPa. The pressed flexible layer is placed in a drying kiln for drying at 300℃×18h, and is used for use after drying.
[0066] The various component raw materials of the contact layer are fully mixed according to the ratio of this embodiment to form a contact layer mixture, and the contact layer mixture is applied to the working hot surface of the flexible layer, and the thickness of the applied contact layer is 3mm. The applied sand mold plate is placed in a drying kiln for drying at 230°C for 3h, and assembled into a sand mold after drying.
[0067] Example 5
[0068] A sand mold material for molten chrome corundum comprises a flexible layer and a contact layer, wherein the flexible layer is composed of the following raw materials, measured in parts by weight:
[0069] Cast chromium oxide aggregate with a particle size of 2.0mm~3.0mm, Cr2O3 content>80%, added in an amount of 30 parts,
[0070] The particle size is 0.5mm~1mm fused-cast chromium oxide aggregate, the Cr2O3 content is greater than 80%, and the addition amount is 15 parts;
[0071] α-alumina powder, particle size requirement: ≤ 0.05mm, addition amount: 45 parts;
[0072] Zircon sand, particle size requirement: 45μm-100μm, added amount 5 parts;
[0073] Mullite fiber, fiber diameter: 0.5mm-0.1mm fiber length: 5mm-10mm, added amount 5 parts;
[0074] The amount of the bonding promoter added is 0.31 parts, and the bonding promoter is composed of yttrium oxide and lanthanum oxide, and the mass ratio of yttrium oxide to lanthanum oxide is 1:2;
[0075] The amount of the binder added is 18 parts, and the binder is mainly composed of aluminum sol and zirconium sol, and the mass ratio of aluminum sol to zirconium sol is 2:1;
[0076] Polyoxyethylene alkylphenol ether, 0.8 parts.
[0077] The contact layer raw materials and the proportions of each component are the same as those in Example 2.
[0078] According to the proportions in this embodiment, chromium oxide aggregates with particle sizes of 2.0mm~3.0mm and 0.5mm~1mm, α-alumina powder, zircon sand, binder, and bonding promoter are mixed, and a mixture is prepared after sufficient mixing. Then, the mullite fiber according to the proportions in this embodiment is added to the stirred mixture, and the polyoxyethylene alkylphenol ether according to this embodiment is added, and the flexible layer mixture is quickly stirred to prepare the flexible layer mixture. The stirred flexible layer mixture is pressurized and molded by a 1000T friction press, and the molding pressure is 220MPa. The pressed flexible layer is placed in a drying kiln for drying at 300℃×18h, and is used for standby after drying.
[0079] The various component raw materials of the contact layer are fully mixed according to the ratio of this embodiment to form a contact layer mixture, and the contact layer mixture is applied to the working hot surface of the flexible layer, and the thickness of the applied contact layer is 3mm. The applied sand mold plate is placed in a drying kiln for drying at 230°C for 3h, and assembled into a sand mold after drying.
[0080] Example 6
[0081] A sand mold material for casting chrome corundum includes a flexible layer and a contact layer. The raw materials and the ratio of each component of the flexible layer are different from those of Example 5 in that a PVC pipe is added to the flexible layer component of this embodiment, and the added amount of the PVC pipe is 3 parts by weight. The remaining components of the flexible layer are the same as those of Example 5.
[0082] The raw materials and proportions of the components of the contact layer are the same as those in Example 2.
[0083] According to the proportions in this embodiment, chromium oxide aggregates with particle sizes of 2.0mm~3.0mm and 0.5mm~1mm, α-alumina powder, zircon sand, PVC pipe, binder and bonding promoter are mixed, and a mixture is prepared after sufficient mixing. Then, mullite fiber according to the proportions in this embodiment is added to the stirred mixture, and polyoxyethylene alkylphenol ether according to the proportions in this embodiment is added, and the fiber mixture is quickly stirred to prepare a fiber mixture. The uniformly stirred flexible layer mixture is pressurized on a 1000T friction press with a molding pressure of 220MPa. The pressed flexible layer is placed in a drying kiln for drying at 300℃×18h, and is used for standby after drying.
[0084] The various components of the contact layer of this embodiment are fully mixed according to the above ratio to form a contact layer mixture, and the contact layer mixture is applied to the working hot surface of the flexible layer, and the thickness of the applied contact layer is 5 mm. The applied sand mold plate is placed in a drying kiln for drying at 230°C for 3 hours, and then assembled into a sand mold after drying.
[0085] After the sand materials obtained in the above embodiments were subjected to high-temperature treatment at 1600°C, the flexural strength and true porosity were tested, and the sand mold prepared from the sand materials was cast (casting time 240s, casting temperature 2055°C). The total thickness of the cast original sand mold plate was 40mm. After casting, the maximum depression depth of the heat flow scouring area of the sand mold plate was measured, and the results were obtained as shown in Table 1.
[0086] Table 1 Test results of sand mold materials in various examples
[0087] Test Project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Flexural strength (MPa) 2.45 3.11 4.62 3.5 5.1 4.9 True porosity (%) 22 22 34.7 50 26 35 Maximum depression depth (mm) 38 26 29 22 12 7
[0088] In the above test results, Example 5 shows the best comprehensive performance. The flexural strength of this formula reaches 5.1 MPa, which is significantly higher than that of other examples: At the same time, its true porosity is 26%, which is between low and high, and can effectively balance the strength and thermal conductivity of the material. In addition, the maximum depression depth of this formula at a high temperature of 1600°C is only 12 mm, indicating its excellent deformation resistance. Overall, the comprehensive indicators of Example 5 are better than other formulas, and can better meet the demanding requirements of high-temperature casting processes.
[0089] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0090] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the inventive concept and technical solution to other occasions without improvement, should be regarded as the protection scope of the present invention.
Claims
1. A sand material, characterized in that: It comprises a flexible layer and a contact layer, wherein the contact layer is coated on the surface of the flexible layer; In parts by weight, The flexible layer comprises: 20 to 50 parts of fused-cast chromium oxide aggregate of the first particle size, 10 to 30 parts of fused-cast chromium oxide aggregate of the second particle size, wherein the second particle size is smaller than the first particle size, 20 to 60 parts of α-alumina powder, 0 to 10 parts of zircon sand, 0 to 15 parts of mullite fiber, 0 to 15 parts of PVC pipe, 0.18 to 0.51 parts of bonding promoter, 5 to 25 parts of bonding agent, and 0 to 2.5 parts of polyoxyethylene alkylphenol ether; The contact layer comprises: 1 to 10 parts of ρ-alumina powder, 30 to 75 parts of α-alumina powder, 20 to 50 parts of chromium micropowder, 5 to 15 parts of zirconium oxide micropowder, 10 to 15 parts of aluminum sol, and 0.5 to 1 part of magnesium oxide micropowder.
2. The sand material according to claim 1, characterized in that: The first particle size ranges from 2.0 mm to 3.0 mm, and the second particle size ranges from 0.5 mm to 1 mm.
3. The sand material according to claim 1, characterized in that: The bonding promoter is composed of yttrium oxide and lanthanum oxide, wherein the mass ratio of yttrium oxide to lanthanum oxide is (0.5-1):
1.
4. The sand material according to claim 1, characterized in that: The binder is composed of aluminum sol and zirconium sol, wherein the mass ratio of aluminum sol to zirconium sol is (1-3):(1-5).
5. The sand material according to claim 1, characterized in that: The particle sizes of the α-alumina powder, chromium powder and zirconium oxide powder are all ≤0.05 mm, and the particle size of the zircon sand is 45 μm to 100 μm.
6. The sand material according to claim 1, characterized in that: The fiber diameter of the mullite fiber is 0.5 mm to 0.1 mm, and the fiber length is 5 mm to 10 mm.
7. The sand material according to claim 1, characterized in that: The PVC tube has a diameter of 2.5 mm to 5.5 mm and a length of 10 mm to 50 mm.
8. A method for preparing a sand material, characterized in that: The following steps are involved: Step 1: preparing a flexible layer, which comprises the following steps, in parts by weight: a) fully mixing 20 to 50 parts of a first-size fused-cast chromium oxide aggregate, 10 to 30 parts of a second-size fused-cast chromium oxide aggregate (the second size is smaller than the first size), 20 to 60 parts of α-alumina powder, 0 to 10 parts of zircon sand, 0 to 15 parts of PVC pipe, 0.18 to 0.51 parts of a bonding promoter, and 5 to 25 parts of a bonding agent to prepare an initial mixture; b) adding 0 to 15 parts of mullite fiber to the initial mixture of step a), and then adding 0 to 2.5 parts of polyoxyethylene alkylphenol ether, and rapidly stirring to prepare a flexible layer mixture; c) pressing the flexible layer mixture through a pressing device; d) placing the pressed flexible layer mixture in a drying kiln for drying to obtain a flexible layer; Step 2: preparing a contact layer, by weight, comprising: uniformly mixing 1 to 10 parts of ρ-alumina powder, 30 to 75 parts of α-alumina powder, 20 to 50 parts of chromium powder, 5 to 15 parts of zirconium oxide powder, 10 to 15 parts of aluminum sol, and 0.5 to 1 part of magnesium oxide powder to prepare a contact layer mixture; Step 3: composite molding, including the following steps: 1) applying the contact layer mixture in step 2 to the surface of the flexible layer prepared in step 1; 2) placing the coated composite layer in a drying kiln to dry to obtain a sand mold material.
9. The preparation method according to claim 8, characterized in that: The contact layer mixture in step 2 is applied to the surface of the flexible layer in step 1 to a coating height of 1 mm to 6 mm.
10. A mold, characterized in that: The sand material according to any one of claims 1 to 7 is used.
Citation Information
Patent Citations
Novel inorganic sand mold binding agent for fused zirconia alumina brick sand mold and sand mold prepared from novel inorganic sand mold binding agent
CN112338818A
A method for preparing a modified water glass combined with white corundum sand mold
CN115321940B